Perceptions of Public School Intermediate-Level Teachers in the Implementation of the Catch–Up Friday Program - Ganohay, Jaris May; Gargar, April May; Cortes, Georgina; Balang, Welma; Valmorida, Francis May (Journal of General Education Science, 2024)
This study explored the perceptions of intermediate-level public school teachers regarding implementing the Catch-Up Day program. Six (6) intermediate-level teachers from a public school participated in this single case study, which aimed to understand teachers' views on the program designed to support struggling learners. Data were collected using an Interview Guide. The findings revealed that teachers view the Catch-Up Day program positively, recognizing its benefits for struggling learners despite it adding to their workload. The key strategies employed by teachers included sharing lesson plans with another teacher, utilizing interactive activities, employing basic reading skills, using peer tutoring strategy, and incorporating enhancement activities. Despite encountering challenges such as increased workload, pupils' poor reading comprehension, lack of parental support, and lack of pupils' interest, teachers managed these obstacles by materials, providing take-home activities, communicating with parents, and providing interactive reading activities. Teachers agreed on the program's effectiveness in improving students' reading skills and emphasized the need for adequate resources and support to ensure its continued success. The recommendations from this study could help educators, school administrators, and policymakers enhance the programs and make adjustments that effectively address the needs of teachers and students.